Utilization of Kahoot Application as a Learning Evaluation Tool on the Basics of Accounting Material for Service Companies in Class X - Wiradinata, Rochanda; Yuningsih, Elis (Annpublisher, 2024)
This study aims to determine the improvement of the Kahoot X application of as a learning evaluation tool on learning the basics of accounting and how students respond to the Kahoot application. In this study, using quantitative methods with an experimental method approach with a research design, one group pretest and one group posttest, with the population in this study being class X totaling 33 students, one class was taken as a purposive research sample. In the data collection technique in this study, using tests, namely pre-tests and post-tests, to find out how students improve and questionnaires to find out their responses. Then for data analysis using several tests, namely validity tests, reability, classical assumption tests, and hypothesis tests. The results showed that the Kahoot evaluation tool significantly affected student learning outcomes. This can be shown from the increased N-Gain value and the acquisition of a calculated T-value of 19.022, which means that the Thichung is greater than the ttabel (19,022 1,697) with a significance of 0.000 less than 0.05. As well as a good response from students, there were results of 70% of students who agreed that the Kahoot application could be used for evaluation tools on learning the basics of accounting. So that the kahoot application can be used as a learning evaluation tool and improve learning outcomes.